STRATEGIC PROJECTS IN CENTRAL ASIA: OPPORTUNITIES AND POTENTIAL RISK ANALYSIS CHALLENGES - Khikmatov Fatkhulla Khabibullaevich (Scholar Express Journal, 2022)
The article mainly analyzes two geopolitical strategies related to the Eurasian region of Russia and China in recent years through trade and energy routes through Central Asia in order to develop economic cooperation between East and West.
Keywords: strategy; geopolitical strategies; geopolitical project; Eurasian Economic Union